Surgical treatment for insertional Achilles tendinopathy and retrocalcaneal bursitis: more than 1 year of follow-up - Zhang, Changgui (J Int Med Res, 2021)
OBJECTIVE: To analyse the imaging changes in bone marrow oedema of the calcaneal prominence, retrocalcaneal bursa and degenerative Achilles tendon after the surgical treatment of insertional Achilles tendinopathy (IAT). METHODS: This retrospective study analysed patients with IAT and retrocalcaneal bursitis that were diagnosed based on their symptoms and radiographic and magnetic resonance imaging (MRI) examinations. For patients that had received 3 months of conservative treatment but still presented with symptoms, arthroscopic debridement of the retrocalcaneal bursa and resection of calcaneal prominence were undertaken. Patients with degeneration of the Achilles tendon underwent debridement of Achilles tendon calcification with an open incision. The last follow-up included radiographic and MRI imaging, Visual Analogue Scale (VAS) pain scores and American Orthopedic Foot and Ankle Society (AOFAS)-Ankle and Hindfoot scores. RESULTS: Thirty patients were included (mean ± SD follow-up, 3.1 ± 0.5 years). The VAS pain and AOFAS-Ankle and Hindfoot scores were significantly improved after surgery. MRI showed that bone marrow oedema of the calcaneal prominence and the retrocalcaneal bursa was significantly reduced compared with preoperative values. There was no significant change in the high signal area of the IAT. CONCLUSION: Surgical treatment of IAT and retrocalcaneal bursitis effectively alleviated local pain and restored function.